Evaluasi Titik Impas Biaya Peledakan Batu Granit Bulan Januari 2017 Melalui Perbaikan Metode Peledakan Pada PT Vitrama Properti Di Desa Air Mesu Kabupaten Bangka Tengah: Evaluation Break Even Point OF Granite Explosion Cost In January 2017 Through Improved Blasting Methods At PT Vitrama Properti In Air Mesu Village District Of Bangka Tengah - Susanto, Hendra; Tono, E.P.S.B Taman; Pitulima, Janiar (MINERAL, 2017)
PT Vitrama Properti is one of the private companies that run on the mining field, namely the mining of natural resources of granites. In this study, the researcher observes the cost of explosion used by PT Vitrama Properti in its mining of granites. According to the economic analysis, to determine the cost of explosion need to count on the breakeven point. The method employed in this research is to analyze the breakeven point. Breakeven point is a calculation used to know the volume of explosion rate so that the total income and total cost will be at the breakeven point. The data collection is conducted from December 2016 to February 2017, including the data of drilling cost, explosion usage cost, the salary of employees and contract employees, excavators and dump trucks fuel cost, equipment ownership cost, and the specification of explosion tools and equipment. The result of the data analysis shows that the total explosion cost paid by PT Vitrama Properti in January 2017 is Rp.1,041,936,063,00 and the total income earned is Rp.1,287,134,940.00, so the total profit made is Rp.245,198,976.00. Whereas, the breakeven point of PT Vitrama Properti in January 2017 is on the explosion volume rate of 23,109.08 m3 with the total earning and total cost is Rp.841,170,781.00. One of the significant factors to reduce the cost of explosion is to improve the geometry of explosion and to make the effective use of ANFO. After implementing the improved geometry of the explosion, the breakeven point is also improved from the volume rate of 23,109.08 m3 to the volume rate of 21,090.35 m3. Also, to increase the income from the explosion process can be done by increasing the sale of granite from the explosion (boulder) into 7,072.17 m3 with the total income of Rp.257,426,988.00, as well as by increasing the total product sale of 24,752.59 m3 with the total income obtained of Rp.900,994,458.00.